2012
DOI: 10.1111/j.1365-2648.2012.06096.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis strategy: building a culturally sensitive mid‐range theory of risk perception using literary, quantitative, and qualitative methods

Abstract: The synthesis strategy is an intensive process for developing a culturally sensitive mid-range theory. Testing of the theory will ascertain its usefulness for reducing health inequalities in vulnerable groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…More educated subjects have a significant amount of previous information regarding the objective risk than those with less education. This is in agreement with the statements of Siaki et al (2013), who suggest that risk appraisals are influenced by affect, health-world views, cultural customs, and protocols that intersect with the health risk. The fact that more educated subjects are more informed than the less educated ones may suggest that education can act as a filter of media information, since one of the effects of the media attention, that has undoubtedly accompanied genetics advances, is the increasing anxiety among a wider range of subjects atrisk (Patenaude, Guttmacher, & Collins, 2002).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…More educated subjects have a significant amount of previous information regarding the objective risk than those with less education. This is in agreement with the statements of Siaki et al (2013), who suggest that risk appraisals are influenced by affect, health-world views, cultural customs, and protocols that intersect with the health risk. The fact that more educated subjects are more informed than the less educated ones may suggest that education can act as a filter of media information, since one of the effects of the media attention, that has undoubtedly accompanied genetics advances, is the increasing anxiety among a wider range of subjects atrisk (Patenaude, Guttmacher, & Collins, 2002).…”
Section: Discussionsupporting
confidence: 76%
“…A culturally sensitive mid-range theory of risk perception, recently proposed by Siaki, Loescher and Trego (2013), suggests that risk appraisals are influenced by affect, health-world views, cultural customs, and protocols that intersect with the health risk. On the other hand, trust in the science behind risk assessments and risk management is possibly more important than social trust, although both types of trust should be considered (Sjöberg, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, a considerable number of participants indicated that they believed several erroneous statements regarding breast lumps, self-help techniques, and futility of treatment for breast cancer. According to culturally sensitive mid-range theories, the strength of cultural beliefs, identity, and values that mediate risk perceptions—such as risk attention and risk awareness—influence health-promoting behaviors [25]. Moreover, previous theories have clearly shown the influence of culture on health behaviors insofar as cultural beliefs triggering or prohibiting certain self-care behaviors in individuals with chronic illnesses [17, 26].…”
Section: Discussionmentioning
confidence: 99%
“…The intervention was a multidisciplinary, theoretically based, and culturally sensitive intervention specifically designed for low-income, ethnic-minority adults and caregivers of minors with mental health and psychiatric conditions [ 49 – 52 ]. Interventions structured in this manner are believed to generate superior outcomes for ethnic minority, low-SES populations that have low trust and high stigma [ 49 – 52 ]. The target population included two groups: adult clients with mental illness and adult parents/caregivers of child clients with mental illness.…”
Section: Methodsmentioning
confidence: 99%